PENGARUH PENGGUNAAN POSTER STUNTING TERHADAP ORANG TUA BAYI BALITA DI PUSKESMAS ALAK KOTA KUPANG - Loriana Lorinda Manalor; Firda Kalsum Kiah; Hadiani (Rena Cipta Mandiri, 2026)
Health interventions spanning form the prenatal period through the first five years of life aim to ensure child survival and improve quality of life. Perental involvement is crucial for meeting nutritional needs, as children require significant attenstion and support during this period of rapid growth and development. This study aimed to examine the relationship between parents knowledge regarding stunting-related posters and their use of these materials at the Alak Community Health Center (Puskesmas). Methods:A descriptive study descriptive design was employed. The study population consistednof all parents of children under five visiting five auxiliary community helaths centers, totaling 616 respondents; the entire population served as the simple. The independent variable was parental knowledge, while the dependent variable was the use of stunting posters. Data were collected via quastionnaires and analyzed using descriptive statistics. Results: The majority of respondents were under 25 years old (n=359;58.3%), had a high school education (n=289; 46.9%), were employed in office jobs (n=375; 60.9%), and possessed good knowledge regarding the posters (n=396; 64.3%). Conclusion: Most parents of children under five demonstrated good knowledge concerning the use of stunting posters. Recommended: Awareness-raising initiatives regarding stunting posters should be conductednto further enhance parental knowledge, thereby improving family nutrition and preventing stunting.